(untitled) (Northern International Medical College Journal, 2025)
Introduction: Dengue is one of the most common viral infections affecting the general population in endemic areas annually. However, it is barely reported in newborns owing to a widespread belief that they are protected from severe viral infections in the first six months of life by the presence of maternal antibodies. Neonate can acquire dengue fever either by transplacental or after birth by mosquito bite. Presentation of neonatal dengue mimics neonatal sepsis. Methodology: This retrospective study was done in Bangladesh Shishu Hospital and Institute over January to December 2023. Here we observe how many neonatal dengue had been admitted during that period and the clinical feature and their outcome. Results: In 2023 total admitted dengue patients in Bangladesh Shishu Hospital and Institute were 2033 among them 7 were neonates (0.344%), during this period total 5099 neonates were admitted, among them 1608 neonates were admitted with the features of sepsis. Out of 7 neonates 6 mothers had positive NS1. Among them all had fever on admission and normal blood pressure during hospital stay. All of them had thrombocytopenia initially without any bleeding manifestation. Four neonates developed warning sign, they had raised S Ferritin level and were treated with dexamethasone. Sepsis was ruled out by septic screening. After treatment 6 neonates got discharged and 1 took LAMA (Leave Against Medical Advice). Follow up after 1 month revealed all are doing well. Conclusion: So, dengue should be kept in mind as differential diagnosis if a neonate presents with fever/rash/thrombocytopenia in dengue season. Northern International Medical College Journal Vol. 15 No. 1-2 July 2023-January 2024, Page 685-687